2006
DOI: 10.1161/circulationaha.105.603050
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Dominant Backward-Propagating “Suction” Wave Responsible for Diastolic Coronary Filling in Humans, Attenuated in Left Ventricular Hypertrophy

Abstract: Background-Coronary blood flow peaks in diastole when aortic blood pressure has fallen. Current models fail to completely explain this phenomenon. We present a new approach-using wave intensity analysis-to explain this phenomenon in normal subjects and to evaluate the effects of left ventricular hypertrophy (LVH). Method and Results-We measured simultaneous pressure and Doppler velocity with intracoronary wires in the left main stem, left anterior descending, and circumflex arteries of 20 subjects after a norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
420
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 350 publications
(437 citation statements)
references
References 29 publications
12
420
2
3
Order By: Relevance
“…Data were recorded and analyzed as described previously. 4 We found that systolic pressure rose progressively in the more peripheral arteries and was 5 mm Hg higher in the radial compared with the brachial artery (PϽ0.002; Table).These findings confirm previous studies showing that there is amplification of brachial systolic pressure and pulse pressure compared with aortic pressure but also indicate that the degree of pressure augmentation between the brachial and radial arteries may be at least as large as the augmentation between the brachial and proximal aortas. These data lend support to the concerns expressed by Segers et al 5 regarding the current practice for the calibration of radial pressure waveforms to brachial artery pressure and directly address the reservations expressed by O'Rourke and Takazawa.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Data were recorded and analyzed as described previously. 4 We found that systolic pressure rose progressively in the more peripheral arteries and was 5 mm Hg higher in the radial compared with the brachial artery (PϽ0.002; Table).These findings confirm previous studies showing that there is amplification of brachial systolic pressure and pulse pressure compared with aortic pressure but also indicate that the degree of pressure augmentation between the brachial and radial arteries may be at least as large as the augmentation between the brachial and proximal aortas. These data lend support to the concerns expressed by Segers et al 5 regarding the current practice for the calibration of radial pressure waveforms to brachial artery pressure and directly address the reservations expressed by O'Rourke and Takazawa.…”
supporting
confidence: 89%
“…Data were recorded and analyzed as described previously. 4 We found that systolic pressure rose progressively in the more peripheral arteries and was 5 mm Hg higher in the radial compared with the brachial artery (PϽ0.002; Table).…”
mentioning
confidence: 78%
“…The most important one may be coronary blood flow. Sun et al [35,36] reported the results of wave intensity separation analysis in dogs, and Davies et al [7] reported those in humans.…”
Section: Separation Of Wave Intensity Into the Forward And Backward Cmentioning
confidence: 99%
“…Our most striking finding was that in patients with obstructive coronary stenoses, cold air during exercise abrogated the adaptive 200% increase in the backward expansion wave that accompanied exercise in room temperature (Figure 6). This microcirculatory “suction” wave results from the release of external compressive forces on resistance vessels during ventricular relaxation,23 which in turn decreases MVR. This wave is the largest magnitude wave in the cardiac cycle and enables early diastolic coronary flow acceleration following aortic valve closure 23…”
Section: Discussionmentioning
confidence: 99%
“…Net coronary wave intensity (dI) was calculated as the product of the derivatives of ensemble‐averaged distal coronary pressure (P d ) and Doppler‐flow velocity (CBF), so that: dI=dP d /dt×dCBF/dt 21. We calculated, as previously described,22, 23 the 2 dominant waves that drive coronary perfusion (Figure 2): (1) The forward compression wave, a systolic acceleratory wave generated by sudden increases in aortic pressure at the inlet during ventricular ejection. (2) The backward expansion wave, an early diastolic acceleratory wave generated by microcirculatory suction from the rapid reduction in left ventricular pressure during ventricular relaxation (relieving compression of intramyocardial vessels) 22, 23…”
Section: Methodsmentioning
confidence: 99%